Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to prove this equation: $$\sin\left(\frac{\pi}{n}\right)\cdot \sin\left(\frac{2\pi}{n}\right) \cdots \sin\left(\frac{(n-1)\pi}{n}\right)=\frac{2n}{2^n}$$ There's a hint: Consider the product of $n-1$ non-zero roots of equation $(z+1)^n=1$, but I fail to understand it.

share|improve this question
    
To begin with, those roots will be given by $z+1=e^{ik/n}$ for $k=1,2,\ldots,n-1$. Does that help? Possibly useful is that these come in complex conjugate pairs (except for one, if $n$ is even). –  Harald Hanche-Olsen May 2 '13 at 13:56

2 Answers 2

up vote 5 down vote accepted

To explain the given hint:

the roots of $x^n=1$ are $$x_k=e^{2ik\pi/n}\quad k=0,\ldots,n-1$$ so the product of roots except $0$ of $(z+1)^n=1$ is $$\prod_{k=1}^{n-1} (x_k-1)=\prod_{k=1}^{n-1}e^{2ik\pi/n}-1=\prod_{k=1}^{n-1}e^{ik\pi/n}\prod_{k=1}^{n-1}(e^{ik\pi/n}-e^{-ik\pi/n})=\prod_{k=1}^{n-1}2ie^{ik\pi/n}\prod_{k=1}^{n-1}\sin({k\pi/n})$$

hence to find the desired result you have to calculate (which isn't difficult) $$\prod_{k=1}^{n-1}(x_k-1)\quad\text{and}\quad \prod_{k=1}^{n-1}2ie^{ik\pi/n}$$

Hint for the first product you can use the Vieta's formulas and I trust you that you understand this second hint.

share|improve this answer
2  
+1 for the carefully calibrated hint. –  Did May 2 '13 at 14:30

We know the roots of $z^n-1=0$ are $e^{\frac{2k\pi i}n}$ where $0\le k<n$

$$\implies z^n-1=\prod_{0\le k<n}(z-e^{\frac{2k\pi i}n})$$

$$(z-1)\sum_{0< r<n}z^r=(z-1)\prod_{0<k<n}(z-e^{\frac{2k\pi i}n})$$

So, $e^{\frac{2k\pi i}n}, (1\le k\le n-1)$ are roots of the equation $\sum_{1\le r\le n-1}z^r=0$

i.e., $\sum_{1\le r\le n-1}z^r=\prod_{0<k<n}(z-e^{\frac{2k\pi i}n})$

$$\text{Putting }z=1 \text{ in the above identity } ,\prod_{1\le k\le n-1}(1-e^{\frac{2k\pi i}n})=n$$

$$\text{ Taking modulus, }\prod_{1\le k\le n-1}\left|1-e^{\frac{2k\pi i}n}\right|=n--->(1)$$

$$\text{ Now, }1-e^{\frac{2k\pi i}n}=1-\left(\cos \frac{2k\pi}n+i\sin\frac{2k\pi}n\right)=2\sin^2\frac{k\pi}n-i2\sin\frac{k\pi}n\cos\frac{k\pi}n$$ $$=-2i\sin\frac{2k\pi}n\left(\cos\frac{k\pi}n-i\sin\frac{k\pi}n\right)$$

$$\prod_{1\le k\le n-1}(1-e^{\frac{2k\pi i}n})=\prod_{1\le k\le n-1}\left(-2i \sin\frac{2k\pi}n\left(\cos\frac{k\pi}n-i\sin\frac{k\pi}n\right)\right)$$

$$\text{ Taking modulus, }\prod_{1\le k\le n-1}\left|1-e^{\frac{2k\pi i}n}\right|=\prod_{1\le k\le n-1}\left|-2i \sin\frac{2k\pi}n\left(\cos\frac{k\pi}n-i\sin\frac{k\pi}n\right)\right|=2^{n-1}\prod_{1\le k\le n-1}\sin\frac{k\pi}n--->(2)$$ as $\sin\frac{k\pi}n>0$ for $1\le k \le n-1$

Compare $(1)$ and $(2)$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.